Growing low-temperature, high-quality silicon-dioxide films by neutral-beam enhanced atomic-layer deposition. (16th October 2019) - Chen, Hua-Hsuan; Toko, Susumu; Ohori, Daisuke; Ozaki, Takuya; Utsuno, Mitsuya; Kubota, Tomohiro; Nozawa, Toshihisa; Samukawa, Seiji
Abstract: A novel deposition technique, called 'neutral-beam enhanced atomic-layer deposition' (NB-EALD), was successfully used to form a high-quality SiO2 layer by using a precursor (BDEAS) and an oxygen neutral beam at room temperature (30 °C). The results demonstrate a typical ALD process and good thickness control at angstrom level. It was found that the properties of the NBEALD-formed SiO2 film (namely, chemical composition, surface roughness, uniformity, density, and wet etch rate) were almost equivalent to those of thermal SiO2 . It is concluded from this result that NBEALD is a promising candidate for high-quality and low-temperature ALD instead of plasma-enhanced ALD and thermal ALD.